PENERAPAN MODEL INTERACTIVE CONCEPTUAL INSTRUCTION (ICI) PADA MATERI ELASTISITAS DI SMA NEGERI 5 PONTIANAK - Ramansyah Ramansyah; Stepanus Sahala Sitompul; Syukran Mursyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to determine the effectiveness of the implementation of interactive conceptual instruction (ICI) models to increase the learning outcomes of the elasticity's material of students in class XI MIA SMA Negeri 5 Pontianak. This reseacrh method is quasi-experimental with non-equivalent control group design. Intact group purposive sampling used in this research with 34 students of XI MIA 2 as experiment class and 35 students of XI MIA 1 as control class. 7 items are used as instrument with each test before and after treatment. Based on the results of analysis an increase in the learning outcomes of control class students by 0.29 (low) and the experimental class by 0.60 (moderate). The results of  calculation of the experimental class gain and control class obtained sig.(2 tailed) of 0,000 < 0,05 it can be concluded that there is a significant differences in student learning outcomes improvement using the ICI model and the effectiveness of using the ICI model is categorized as high with effect size 3.30 (high category). Based on these results show that the impelementation of the ICI model is effective in improving students learning outcomes the material elasticity in SMA Negeri 5 Pontianak.Keywords :  Effectiveness, Elasticity, Improved Learning Outcomes, Interactive Conceptual Instruction.